Sex-Based Differences in Left Ventricular Assist Device Utilization: Insights From the Nationwide Inpatient Sample 2004 to 2016. (September 2019) - Joshi, Aditya A.; Lerman, Joseph B.; Sajja, Aparna P.; Dahiya, Garima; Gokhale, Avantee V.; Dey, Amit K.; Kyvernitakis, Andreas; Halbreiner, M. Scott; Bailey, Stephen; Alpert, Craig M.; Poornima, Indu G.; Murali, Srinivas; et al.
Abstract : Background: Women comprise approximately one-third of the advanced heart failure population but may receive fewer advanced heart failure therapies including left ventricular assist devices (LVADs). During the early pulsatile-flow device era, women had higher post-LVAD mortality and increased complications. However, knowledge about these differences in the continuous-flow device era is limited. Therefore, we sought to explore temporal trends in LVAD utilization and post-LVAD mortality by sex. Methods and Results: Patients with LVAD implantation from 2004 to 2016 were identified using the Nationwide Inpatient Sample. Trends in LVAD utilization and post-LVAD inpatient mortality were compared by sex and device era. Although LVADs are being increasingly utilized for patients with advanced systolic heart failure, women continue to represent a smaller proportion of LVAD recipients—25.8% in 2004 to 21.9% in 2016 ( P for trend, 0.91). Women had increased inpatient mortality after LVAD implantation compared with men in the pulsatile-flow era (46.9% versus 31.1%, P <0.0001) but not in the continuous-flow era (13.3% versus 12.1%, P =0.27; P for interaction=0.0002). Inpatient mortality decreased for both sexes over time after LVAD, with a sharp fall in 2008 to 2009. Female sex was independently associated with increased post-LVAD inpatient mortality beyond adjustment for demographics and risk factors during the pulsatile-flow era (odds ratio, 2.13; 95% CI, 1.45–3.10; P <0.0001) but not during the continuous-flow era (1.18; 0.93–1.48; P =0.16). Conclusions: Although utilization of LVAD therapy increased over time for both sexes, LVAD implantation remains stably lower in women, which may suggest a potential underutilization of this potentially life-saving therapy. Prospective studies are needed to confirm these findings. Abstract : Supplemental Digital Content is available in the text.